Locals' attitudes toward mass and alternative tourism: The case of Sunshine Coast, Australia - Gursoy, D; Chi, C.; Dyer, P. (SAGE Publications, 2010)
This study examines local residents' attitudes toward two different types of tourism development, mass tourism and alternative tourism, using data collected from residents of Sunshine Coast, Australia. The study findings reveal that host community support is affected directly and/or indirectly by the level of community concern, community attachment, ecocentric values, use of the tourism resource base, state of the local economy, and the perceived impacts of tourism development. Findings suggested that even though some of the factors influence attitudes toward both mass and alternative tourism, attitudes toward each form of development is likely to be formed based on the perceptions of different factors. © 2010 SAGE Publications.